PENGARUH FASILITAS BELAJAR TERHADAP MOTIVASI BELAJAR SISWA (Survey kelas X IPS SMA Negeri 1 Ngamprah) - Ani Setiani; Yudho Ramafrizal; Dian Prihatin (Sekolah Tinggi Pariwisata Mataram, 2022)
The title of this research is The Effect of School Learning Facilities on Student Motivation (a survey of class X IPS SMA Negeri 1 Ngamprah). This study aims to (i) determine the school learning facilities at SMA Negeri 1 Ngamprah (ii) determine the level of student motivation at SMA Negeri 1 Ngamprah (iii) determine the effect of school learning facilities on student learning motivation at SMA Negeri 1 Ngamprah. This study the author uses a quantitative approach using survey research methods, with a sample of 60. To find the effect, the data analysis used is simple linear regression analysis using SPSS 25, recapitulation of descriptive analysis of school learning facilities with a total weight of 40.86 and a value an average of 4.08, and student learning motivation with a total weight of 44.83 and an average value of 4.18, in the simple linear regression test there is a regression coefficient value obtained is 0.665, and the coefficient of determination is obtained the R number (correlation coefficient) or the number of relationships between variable X and variable Y is 0.702 or 70.2%. The amount of contribution made by the school learning facilities variable can be seen from the figure on the R Square, which is 0.493 which means that school learning facilities affect student learning motivation by 49.3%. While the other 50.7% is influenced by other factors outside of the research conducted.